Allergic Contact Dermatitis to a Laptop Computer in a Child. Issue 3 (6th March 2014) - Jacob, Sharon E.; Admani, Shehla
Abstract This report details the case of an 11‐year‐old boy with a history of atopic dermatitis who developed a widespread dermatitis 1 month after receiving a laptop for Christmas. Allergic contact dermatitis to nickel in the laptop was determined as the cause.